Deep-water Thyasiridae (Mollusca: Bivalvia) from the Oman Margin, Arabian Sea, new species and examples of endemism and cosmopolitanism - Oliver, P. Graham (Zootaxa, 2015)
Seven species of Thyasiridae are reported from the Oman Margin of the Arabian Sea at depths between 688 m and 3356 m. Hypoxic conditions exist at depths between 400 and 1200 m and three species are restricted to this zone and to the Arabian Sea. Leptaxinus indusarium has also been recorded from the Indus Fan and Channelaxinus investigatoris from off Sri Lanka. A new species Thyasira anassa sp. nov. is described from the hypoxic zone. Another four species are recorded from the abyssal zone where oxygen levels are typical for the deep ocean. Here another new species is described, Parathyasira bamberi sp. nov. but the other species could not be conclusively identified because of close affinity with populations from other oceans.  Deep water Atlantic species Axinulus croulinensis and Mendicula ferruginosa are apparently present in the abyssal Indian Ocean while another thyasirid shell is very close to Channelaxinus excavatus from the Eastern Pacific and C. perplicata from the Atlantic. Accompanying these abyssal thyasirids were other bivalve species, Deminucula atacellana, Limopsis pelagica and Bentharca asperula that cannot be distinguished by morphology from their Atlantic populations. It is concluded that using morphology alone that the abyssal species may well be cosmopolitan in distribution.